Rapid and Reliable Data Treatment for the Control of Food Chemical Contaminants by LC-HRMS. Issue 11 (2nd November 2022) - Carreres, Benoît M.; Bessaire, Thomas; Desmarchelier, Aurélien; Mottier, Pascal; Delatour, Thierry
Abstract: Liquid chromatography-high resolution mass spectrometry (LC-HRMS) is considered an unavoidable extension of low-resolution LC-MS/MS that stretches the capabilities of multi-residue analysis of chemical contaminants in food. However, LC-HRMS acquisitions generate a massive amount of information available for data processing with supplier software that still miss critical calculation features and adapted reporting tools. Consequently, routine laboratories are still reluctant to switch from LC-MS/MS to LC-HRMS, the latter is still perceived as a cumbersome and demanding technology. In that context, we propose a four-step LC-HRMS workflow to speed-up data processing in situations of multi-residue multi-matrix analysis with the goal to maximize the time spent on data interpretation rather than on data formatting. The first three steps of the workflow imply specific settings on the Orbitrap HRMS associated software (TraceFinder TM ) while the fourth step is the novelty i.e. a newly coded R-script capable to translate a raw export file into a comprehensive .xlsx report file in a few seconds. As recommended by various international guidelines and in some official methods, standard addition-based applications are fully embedded in this reporting tool whilst still being the main bottleneck of supplier's software. The reporting tool also allows appropriate data formatting, filtering, and color-coding options to provide a clear picture of compounds being detected or not, and those requiring specific attention due to unmet quality control criteria as required by European legislation (European Commission SANTE 11312/2021). It is hoped that additional functionalities compatible with R scripts will be soon fully embedded in the supplier's software for easier data interpretation and reporting.